Gayo merangkai identitas - Wiradnyana, Ketut, 1966-; Setiawan, Taufiqurrahman, 1982- (Jakarta : Yayasan Pustaka Obor Indonesia, 2011)
On prehistoric life of Gayo people in Aceh Tengah, Indonesia.
Includes bibliographical references (p. 158-163) and index.
Keywords: Gayo (Indonesian people) -- History; Prehistoric peoples -- Indonesia -- Aceh Tengah; Antiquities, prehistoric -- Indonesia -- Aceh Tengah; Aceh Tengah (Indonesia) -- History